Porous material with oil absorption performance and preparation method and application thereof
By loading MXene nanomaterials and alkyl silane coupling agent on the porous material substrate, an efficient oil-absorbing material is formed, which solves the problems of low adsorption efficiency and secondary pollution in the prior art, and achieves efficient and economical oil-containing wastewater treatment.
Patent Information
- Application Number
- CN202411446461.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-10
AI Technical Summary
The existing porous materials have low adsorption efficiency, high cost, difficult to recycle and utilize when treating oil-containing sewage, and have secondary pollution problems.
The porous material substrate is loaded with MXene nanomaterials and alkyl silane coupling agent, and the silane coupling agent is loaded onto the porous material through chemical vapor deposition to form an oil-absorbing material with hydrophobicity and high surface area, improving adsorption selectivity and realizing the material. reuse.
It significantly improves the adsorption capacity and selectivity to the oil phase, reduces the treatment cost, avoids secondary pollution, and the material can be reused and has high adsorption efficiency.
Smart Images

Figure CN119281304A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adsorption materials, and in particular relates to a porous material with oil absorption performance and a preparation method and application thereof. Background Art
[0002] With the acceleration of industrialization and urbanization, the discharge of oily wastewater has become one of the main sources of water pollution, seriously threatening human health and the safety of aquatic ecosystems. In this context, the technology of oil-water separation using bionic highly selective adsorption materials has emerged. The purpose and significance of using adsorption materials to solve sewage treatment problems are far-reaching and extensive. It is not only an urgent need to protect the water environment and maintain ecological balance, but also an important way to achieve resource recovery and reuse, promote technological innovation and industrial upgrading, and a key measure to promote sustainable economic and social development.
[0003] Due to the high viscosity of crude oil, most adsorbent materials cannot effectively separate crude oil / water mixtures. Since crude oil easily contaminates the absorbent material, the migration and diffusion of heavy oil into the pores and channels of the adsorbent material is greatly reduced, the adsorption efficiency is low, and the clean treatment and recovery of the adsorbent material are difficult.
[0004] The prior art reports the following methods to deal with the above problems, such as in-situ combustion, gravity, microbial degradation, skimming and adsorption separation, which have been used to repair immiscible crude oil / water mixtures. However, the above methods have disadvantages such as low separation efficiency, large air pollution and high operating costs. For example, incomplete combustion of crude oil will release toxic gases that pollute the air; microbial degradation and skimming are time-consuming. Adsorption has the problems of low adsorption efficiency, limited adsorption capacity and difficult regeneration.
[0005] In addition, conventional adsorption materials such as straw, leaves, and oil-absorbing felt have low separation selectivity and adsorption capacity because they adsorb both water and oil. The prior art has proposed methods such as adding chemical demulsifiers and electrolytic demulsifiers to separate emulsified crude oil / water mixtures. However, the electrolytic method consumes a lot of energy, the demulsifier is difficult to recycle, and is even harmful to the environment. Summary of the invention
[0006] The present application provides a porous material with oil absorption performance, a preparation method and application thereof, aiming to solve the problems of low adsorption efficiency, high cost, difficulty in recycling and secondary pollution of existing porous materials when treating oily wastewater.
[0007] In a first aspect, the present application provides a porous material with oil absorption performance, including a porous material substrate, a MXene nanomaterial and an alkyl silane coupling agent loaded on the porous material substrate.
[0008] The porous material with oil absorption performance described in the present application has a porous structure and has strong hydrophobicity. The loading of the alkylsilane coupling agent can change the structure and surface hydrophilic-hydrophobic properties of the porous material surface. The porous structure of the porous material gives it a large surface area, thereby increasing the adsorption capacity for liquids. The super-strong hydrophobicity of the porous material enables it to effectively adsorb the oil phase in the oily wastewater, greatly improving the adsorption selectivity of the porous material, making it highly adsorbable to the oil phase, and can be reused, and no secondary pollution will be generated during the treatment of oily wastewater.
[0009] According to some embodiments of the porous material having oil absorption properties described in the present application, the porous material substrate includes one or more of a polyurethane sponge substrate, a melamine sponge substrate and a wood sponge.
[0010] According to some embodiments of the porous material having oil absorption properties described in the present application, the silane coupling agent includes one or more of methyltrimethoxysilane, ethyltrimethoxysilane and n-octyltrimethoxysilane.
[0011] According to some embodiments of the porous material with oil absorption properties described in the present application, the loading amount of the MXene nanomaterial on the porous material substrate is 1%-3% of the weight of the porous material substrate.
[0012] According to some embodiments of the porous material with oil absorption performance described in the present application, the loading amount of the silane coupling agent on the porous material substrate is 0.04%-0.06% of the weight of the porous material substrate.
[0013] According to some embodiments of the porous material with oil absorption performance described in the present application, the silane coupling agent is distributed in a gradient on the porous material substrate, and the loading amount of the silane coupling agent gradually decreases from the surface to the interior of the porous material substrate.
[0014] The second aspect of the present application provides a method for preparing the porous material with oil absorption performance according to the first aspect of the present application, comprising the following steps:
[0015] (1) soaking the porous material substrate in an aqueous solution of MXene nanomaterials, and drying the substrate after soaking to obtain a porous material loaded with MXene nanomaterials;
[0016] (2) Loading the silane coupling agent onto the porous material loaded with the MXene nanomaterial by chemical vapor deposition to obtain the porous material with oil absorption performance.
[0017] The preparation method described in the present application can effectively and stably load MXene nanomaterials onto a porous material substrate, and the operation is simple. When a silane coupling agent is loaded onto a porous material substrate by chemical vapor deposition, the properties of the silane coupling agent itself make the porous material substrate have hydrophilic and oleophobic properties, and can prevent the MXene nanomaterial from being oxidized.
[0018] According to some embodiments of the method for preparing a porous material with oil absorption properties described in the present application, in step (1), the concentration of the MXene nanomaterial aqueous solution is 3 mg / ml-7 mg / ml.
[0019] According to some embodiments of the method for preparing a porous material with oil absorption properties described in the present application, the volume ratio of the porous material substrate and the MXene nanomaterial aqueous solution is 1:(1.2-2).
[0020] According to some embodiments of the method for preparing the porous material with oil absorption performance described in the present application, the immersion temperature is 25° C.-35° C., and the immersion time is 4 min-6 min.
[0021] According to some embodiments of the method for preparing the porous material with oil absorption performance described in the present application, the drying temperature is 50° C.-70° C., and the drying time is 50 min-70 min.
[0022] According to some embodiments of the method for preparing a porous material with oil absorption properties described in the present application, in step (2), the surface of the porous material loaded with MXene nanomaterials is wrapped and then subjected to chemical vapor deposition.
[0023] According to some embodiments of the method for preparing a porous material with oil absorption performance described in the present application, the area of the porous material loaded with MXene nanomaterials that is wrapped accounts for 80%-90% of its total surface area.
[0024] According to some embodiments of the method for preparing a porous material with oil absorption performance described in the present application, a plastic wrap is used to wrap the surface of the porous material loaded with MXene nanomaterials.
[0025] According to some embodiments of the method for preparing a porous material with oil absorption properties described in the present application, in step (2), the weight ratio of the silane coupling agent to the porous material loaded with MXene nanomaterial is (0.8-1.2):2000.
[0026] According to some embodiments of the method for preparing a porous material with oil absorption performance described in the present application, the temperature of the vapor deposition is 25° C.-35° C.; and the time of the vapor deposition is 1 h-1.5 h.
[0027] According to some embodiments of the method for preparing the porous material with oil absorption performance described in the present application, the preparation method further includes cleaning the porous material substrate.
[0028] According to some embodiments of the method for preparing the porous material with oil absorption performance described in the present application, the porous material substrate is subjected to ultrasonic cleaning treatment in water and ethanol in sequence.
[0029] The third aspect of the present application provides a method for treating oily wastewater, wherein the oily wastewater is treated with oil absorption by using the porous material with oil absorption properties described in the first aspect of the present application or the porous material with oil absorption properties obtained by the preparation method described in the second aspect of the present application.
[0030] According to some embodiments of the treatment method described in the present application, the viscosity of the oil in the oily wastewater is 0-2500 mPas.
[0031] According to some embodiments of the treatment method described in this application, the concentration of oil in the oily wastewater is greater than 10 ml / m 3 .
[0032] According to some embodiments of the treatment method described in the present application, the treatment temperature is 20°C-90°C, and the treatment time is 4-6 minutes.
[0033] According to some embodiments of the treatment method described in the present application, the treatment is performed under light conditions, preferably, the light intensity is 60mw / cm 2 -150mw / cm 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a SEM image of the porous material prepared in Example 1 of the present application, and the upper right corner is an enlarged image of the marked area;
[0035] Figure 2 This is an analysis diagram of the crude oil adsorption effect of the porous material described in Example 1 of the present application;
[0036] Figure 3 This is an analysis diagram of the effect of temperature on the crude oil adsorption effect of the porous material described in Example 1 of the present application;
[0037] Figure 4 This is an analysis diagram of the effect of light on the crude oil adsorption effect of the porous material described in Example 1 of the present application;
[0038] Figure 5 This is a performance analysis diagram of the porous material reuse described in Example 1 of the present application;
[0039] Figure 6This is an analysis chart of the adsorption capacity of the porous material described in Example 1 of the present application;
[0040] Figure 7 This is an analysis diagram of the adsorption effect of the porous material described in Example 5 of the present application on n-hexadecane. DETAILED DESCRIPTION
[0041] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0042] The technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings.
[0043] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0044] The present application provides a porous material with oil absorption performance, including a porous material substrate, a MXene nanomaterial and an alkyl silane coupling agent loaded on the porous material substrate.
[0045] The porous material described in the present application has a porous structure and has strong hydrophobicity. The porous structure of the porous material gives it a large surface area, thereby increasing its adsorption capacity for liquids. The ultra-strong hydrophobicity of the porous material enables it to effectively adsorb the oil phase in the oily wastewater, greatly improving the adsorption selectivity of the porous material, making it highly adsorbable to the oil phase, and can be reused, without generating secondary pollution in the process of treating the oily wastewater.
[0046] In some embodiments, the porous material substrate includes one or more of a polyurethane sponge substrate, a melamine sponge substrate, and a wood sponge.
[0047] In some embodiments, the silane coupling agent includes one or more of methyltrimethoxysilane, ethyltrimethoxysilane and n-octyltrimethoxysilane. The above silane coupling agent can be loaded on the porous material substrate through a chemical reaction coating method to make the surface of the porous material present hydrophobic and oleophilic properties. The loading of the alkylsilane coupling agent can isolate the MXene nanomaterial from contact with the air, and has the effect of preventing the MXene nanomaterial from aging.
[0048] In some embodiments, the loading amount of the MXene nanomaterial on the porous material substrate is 1%-3% of the weight of the porous material substrate, such as 1%, 2%, 3%, etc. The photothermal effect of the porous material can be effectively improved by adjusting the loading amount of the MXene nanomaterial. When the loading amount is small, the photothermal effect will be reduced, and the required temperature will not be reached, and the porous material will not be able to effectively reduce the viscosity of the crude oil; when the loading amount is large, the load will be unstable and fall off during the application process.
[0049] In some embodiments, the loading amount of the silane coupling agent on the porous material substrate is 0.04%-0.06% of the weight of the porous material substrate, for example, 0.04%, 0.05%, 0.06%, etc. Since the main function of the silane coupling agent is to change the structure and surface hydrophilic and hydrophobic properties of the porous material surface. The silane coupling agent used in this application is an alkane chain silane coupling agent, which has good hydrophobic properties, but also has a certain oleophobicity. The loading amount of the above silane coupling agent helps the porous material achieve a good hydrophobic and oil-absorbing effect.
[0050] In some embodiments, the silane coupling agent is distributed in a gradient on the porous material substrate, and the loading amount of the silane coupling agent gradually decreases from the surface to the interior of the porous material substrate. The gradient distributed silane coupling agent constructs a chemical energy gradient on the porous material, which can increase the oil absorption rate of the porous material.
[0051] The present application also provides a method for preparing the porous material according to the first aspect of the present application, comprising the following steps:
[0052] (1) soaking the porous material substrate in an aqueous solution of MXene nanomaterials, and drying the substrate after soaking to obtain a porous material loaded with MXene nanomaterials;
[0053] (2) Loading the silane coupling agent onto the porous material loaded with the MXene nanomaterial by chemical vapor deposition to obtain the porous material with oil absorption performance.
[0054] The preparation method described in the present application can effectively and stably load MXene nanomaterials onto a porous material substrate, and the operation is simple. When a silane coupling agent is loaded onto a porous material substrate by chemical vapor deposition, the properties of the silane coupling agent itself make the porous material substrate have hydrophilic and oleophobic properties, and can prevent the MXene nanomaterial from being oxidized.
[0055] In some embodiments, in step (1), the mass concentration of the MXene nanomaterial aqueous solution is 3 mg / ml-7 mg / ml; for example, 3 mg / ml, 4 mg / ml, 5 mg / ml, 6 mg / ml, 7 mg / ml, etc.
[0056] In some embodiments, the volume ratio of the porous material substrate and the MXene nanomaterial aqueous solution is 1:(1.2-2); for example, 1:1.2, 1:1.5, 1:1.6, 1:1.8, 1:2, etc.
[0057] In some embodiments, the soaking temperature is 25°C-35°C, such as 25°C, 28°C, 30°C, 32°C, 35°C, etc., and the soaking time is 4min-6min, such as 4min, 5min, 6min, etc.
[0058] In some embodiments, the drying temperature is 50°C-70°C, for example, 50°C, 55°C, 58°C, 60°C, 70°C, etc., and the drying time is 50min-70min, for example, 50min, 55min, 60min, 65min, 70min, etc.
[0059] In some embodiments, in step (2), the surface of the porous material loaded with MXene nanomaterials is wrapped and then chemical vapor deposition is performed. Preferably, the area of the porous material surface loaded with MXene nanomaterials that is wrapped accounts for 80%-90% of its total surface area. For example, 80%, 82%, 85%, 88%, 90%, etc. When the surface of the porous material loaded with MXene nanomaterials is wrapped, during vapor deposition, the vaporized alkylsilane coupling agent can only diffuse from the unwrapped surface of the substrate material to the inside of the substrate material, and the position of the substrate material that first contacts the alkylsilane coupling agent has the longest exposure time to the alkylsilane coupling agent atmosphere, resulting in the largest number of alkylsilane coupling agent components at this position, thus forming a gradient distribution of the alkylsilane coupling agent in the substrate material, thereby making the porous material product have a chemical energy gradient, and the chemical energy gradient can increase the oil absorption rate of the porous material product.
[0060] In some embodiments, the surface of the porous material loaded with MXene nanomaterials is wrapped with plastic wrap.
[0061] In some embodiments, in step (2), the weight ratio of the silane coupling agent to the porous material loaded with MXene nanomaterial is (0.8-1.2):2000, for example, 0.8:2000, 1:2000, 1.2:2000, etc.
[0062] In some embodiments, the temperature of the vapor deposition is 25°C-35°C, such as 25°C, 28°C, 30°C, 32°C, 35°C, etc., and the time of the vapor deposition is 1h-1.5h, such as 1h, 1.2h, 1.3h, 1.5h, etc. Since the silane coupling agent used in this application has a certain volatility, the above temperature can effectively control the volatilization of the silane coupling agent and further control its loading amount.
[0063] In some embodiments, the preparation method further comprises cleaning the porous material substrate.
[0064] In some embodiments, the porous material substrate is ultrasonically cleaned in water and ethanol in sequence, specifically: the porous material substrate is ultrasonically cleaned in ultrapure water for 20 minutes, and then ultrasonically cleaned in ethanol for 20 minutes, and after the ultrasonic cleaning is completed, it is dried in an oven at a working temperature of 60° C. for 2 hours.
[0065] The present application also provides a method for treating oily wastewater, which uses the porous material with oil absorption properties described in the first aspect of the present application or the porous material with oil absorption properties obtained by the preparation method described in the second aspect of the present application for treatment.
[0066] Since the porous material described in the present application has a large surface area and a relatively large oil adsorption capacity, the porous material described in the present application is used to treat oily wastewater, with a relatively high oil absorption efficiency, no secondary pollution, and can be reused.
[0067] In some embodiments, the viscosity of the oil in the oily wastewater is 0-2500 mPas, for example, 20 mPas, 50 mPas, 80 mPas, 100 mPas, 500 mPas, 800 mPas, 1000 mPas, 1200 mPas, 1500 mPas, 1800 mPas, 2000 mPas, 2500 mPas, etc.
[0068] In some embodiments, the oil concentration in the oily wastewater is greater than 10 ml / m 3 , for example 12ml / m 3 , 15ml / m 3 、20ml / m 3 , 25ml / m 3 , 28ml / m 3 、30ml / m 3 、35ml / m3 wait.
[0069] In some embodiments, the treatment temperature is 20°C-90°C, such as 20°C, 30°C, 50°C, 80°C, 90°C, etc., and the treatment time is 4-6 min, such as 4 min, 5 min, 6 min, etc.
[0070] In some embodiments, the treatment is performed under light conditions, preferably, the light intensity is 60 mw / cm 2 -150mw / cm 2 , for example 60mw / cm 2 、70mw / cm 2 、80mw / cm 2 、85mw / cm 2 、90mw / cm 2 、100mw / cm 2 、120mw / cm 2 、135mw / cm 2 、150mw / cm 2 etc. Because MXene materials have photothermal effects, under light conditions, as the temperature rises, the heat energy absorbed by crude oil is converted into intermolecular kinetic energy, and its thermal motion increases, which is manifested in the macroscopic decrease of crude oil viscosity. The decrease in viscosity enhances the fluidity of crude oil and makes it easier to be absorbed by porous media or adsorbents. Therefore, the viscosity of crude oil can be reduced by light, which increases the diffusion rate and permeability of crude oil in porous media.
[0071] Example 1
[0072] A method for preparing a porous material with oil absorption performance comprises the following steps:
[0073] (1) Slowly add 0.8g LiF to 20mL 9mol / L HCl solution, react at 37°C for 10min, then add 0.3g Ti3AlC2 and continue to react at 37°C for 24h. After the reaction is completed, centrifuge the reaction product at 4000rpm. Discard the supernatant, wash the solid residue with ultrapure water, centrifuge again at 4000rpm, and repeat the operation until the solid residue adheres to the wall of the centrifuge tube. Adjust the centrifuge speed to 8000rpm, centrifuge again, discard the supernatant, wash the precipitate with ultrapure water, and repeat the operation until the pH of the supernatant after centrifugation is greater than 5. Add the precipitate after centrifugation to 35ml of ultrapure water, ultrasonically treat for 13min, centrifuge again at 4000rpm for 20min, take the supernatant, and obtain a MXene nanomaterial aqueous solution with a concentration of 5mg / ml;
[0074] (2) Ultrapure water was used to ultrasonically clean a commercially available PU sponge. The PU sponge was a square of 2cm*2cm*2cm and weighed 0.25g. Ultrasonic cleaning was performed for 20 minutes, and then ultrasonic cleaning was performed in ethanol for 20 minutes. After ultrasonic cleaning was completed, the sponge was dried in an oven at a working temperature of 60°C for 2 hours. The cleaned PU sponge was placed in a 5mg / ml MXene nanomaterial aqueous solution obtained in step (1). The weight ratio of the MXene nanomaterial aqueous solution to the PU sponge was 1.2:1. The sponge was soaked at 25°C for 5 minutes, and then dried in an oven at a working temperature of 60°C for 1 hour. After drying, the sponge was soaked in the MXene aqueous solution again. The soaking and drying cycle was repeated 4 times to obtain a porous material loaded with MXene nanomaterials with a MXene nanomaterial loading of 2% of the weight of the porous material substrate, which was recorded as MXene@PU.
[0075] (3) Wrap the surface of the MXene@PU in step (2) with plastic wrap, with the wrapping area accounting for 85% of the total surface area of the MXene@PU, and fix the wrapped MXene@PU on the top of a container such as polytetrafluoroethylene by pasting, and add 50ul of n-octyltrimethoxysilane to the container, and load n-octyltrimethoxysilane onto the porous material by chemical vapor deposition at a temperature of 30°C for 75min to obtain a porous material with an n-octyltrimethoxysilane loading of 0.05% of the weight of the porous material substrate, recorded as OTMS-MXene@PU.
[0076] The SEM image of the porous material described in Example 1 is as follows Figure 1 As shown, from Figure 1 It can be seen that the MXene nanomaterial and the silane coupling agent are both loaded on the porous material.
[0077] Example 2
[0078] The difference between Example 2 and Example 1 is that the temperature of chemical vapor deposition in step (3) is different. The specific operation is as follows:
[0079] A method for preparing a porous material with oil absorption performance comprises the following steps:
[0080] (1) Slowly add 0.8g LiF to 20mL 9mol / L HCl solution, react at 37°C for 10min, then add 0.3g Ti3AlC2 and continue to react at 37°C for 24h. After the reaction is completed, centrifuge the reaction product at 4000rpm. Discard the supernatant, wash the solid residue with ultrapure water, centrifuge again at 4000rpm, and repeat the operation until the solid residue adheres to the wall of the centrifuge tube. Adjust the centrifuge speed to 8000rpm, centrifuge again, discard the supernatant, wash the precipitate with ultrapure water, and repeat the operation until the pH of the supernatant after centrifugation is greater than 5. Add the precipitate after centrifugation to 35ml of ultrapure water, ultrasonically treat for 13min, centrifuge again at 4000rpm for 20min, take the supernatant, and obtain a MXene nanomaterial aqueous solution with a concentration of 5mg / ml;
[0081] (2) Ultrapure water was used to ultrasonically clean a commercially available PU sponge. The PU sponge was a square of 2cm*2cm*2cm and weighed 0.25g. Ultrasonic cleaning was performed for 20 minutes, and then ultrasonic cleaning was performed in ethanol for 20 minutes. After ultrasonic cleaning was completed, the sponge was dried in an oven at a working temperature of 60°C for 2 hours. The cleaned PU sponge was placed in a 5mg / ml MXene nanomaterial aqueous solution obtained in step (1). The weight ratio of the MXene nanomaterial aqueous solution to the PU sponge was 1.2:1. The sponge was soaked at 25°C for 5 minutes, and then dried in an oven at a working temperature of 60°C for 1 hour. After drying, the sponge was soaked in the MXene aqueous solution again. The soaking and drying cycle was repeated 4 times to obtain a porous material loaded with MXene nanomaterials with a MXene nanomaterial loading of 2% of the weight of the porous material substrate, which was recorded as MXene@PU.
[0082] (3) Wrap the surface of the MXene@PU in step (2) with plastic wrap, with the wrapping area accounting for 85% of the total surface area of the MXene@PU, and fix the wrapped MXene@PU on the top of a container such as polytetrafluoroethylene by pasting, and add 50ul of n-octyltrimethoxysilane to the container, and load n-octyltrimethoxysilane onto the porous material by chemical vapor deposition at a temperature of 25°C for 75min to obtain a porous material with an n-octyltrimethoxysilane loading of 0.05% of the weight of the porous material substrate, recorded as OTMS-MXene@PU.
[0083] Example 3
[0084] The difference between Example 3 and Example 1 is only the time of vapor deposition. The specific operation is as follows:
[0085] A method for preparing a porous material with oil absorption performance comprises the following steps:
[0086] (1) Slowly add 0.8g LiF to 20mL 9mol / L HCl solution, react at 37°C for 10min, then add 0.3g Ti3AlC2 and continue to react at 37°C for 24h. After the reaction is completed, centrifuge the reaction product at 4000rpm. Discard the supernatant, wash the solid residue with ultrapure water, centrifuge again at 4000rpm, and repeat the operation until the solid residue adheres to the wall of the centrifuge tube. Adjust the centrifuge speed to 8000rpm, centrifuge again, discard the supernatant, wash the precipitate with ultrapure water, and repeat the operation until the pH of the supernatant after centrifugation is greater than 5. Add the precipitate after centrifugation to 35ml of ultrapure water, ultrasonically treat for 13min, centrifuge again at 4000rpm for 20min, take the supernatant, and obtain a MXene nanomaterial aqueous solution with a concentration of 5mg / ml;
[0087] (2) Ultrapure water was used to ultrasonically clean a commercially available PU sponge. The PU sponge was a square of 2cm*2cm*2cm and weighed 0.25g. Ultrasonic cleaning was performed for 20 minutes, and then ultrasonic cleaning was performed in ethanol for 20 minutes. After ultrasonic cleaning was completed, the sponge was dried in an oven at a working temperature of 60°C for 2 hours. The cleaned PU sponge was placed in a 5mg / ml MXene nanomaterial aqueous solution obtained in step (1). The weight ratio of the MXene nanomaterial aqueous solution to the PU sponge was 1.2:1. The sponge was soaked at 25°C for 5 minutes, and then dried in an oven at a working temperature of 60°C for 1 hour. After drying, the sponge was soaked in the MXene aqueous solution again. The soaking and drying cycle was repeated 4 times to obtain a porous material loaded with MXene nanomaterials with a MXene nanomaterial loading of 2% of the weight of the porous material substrate, which was recorded as MXene@PU.
[0088] (3) Wrap the surface of the MXene@PU in step (2) with plastic wrap, with the wrapping area accounting for 85% of the total surface area of the MXene@PU, and fix the wrapped MXene@PU on the top of a container such as polytetrafluoroethylene by pasting, and add 50ul of n-octyltrimethoxysilane to the container, and load n-octyltrimethoxysilane onto the porous material by chemical vapor deposition at a temperature of 30°C for 60min to obtain a porous material with an n-octyltrimethoxysilane loading of 0.05% of the weight of the porous material substrate, recorded as OTMS-MXene@PU.
[0089] Example 4
[0090] The only difference between Example 4 and Example 1 is that the surface of MXene@PU is not wrapped during the preparation of the porous material.
[0091] Example 5
[0092] The difference between Example 5 and Example 1 is that the temperature of chemical vapor deposition in step (3) is different. The specific operation is as follows:
[0093] A method for preparing a porous material with oil absorption performance comprises the following steps:
[0094] (1) Slowly add 0.8g LiF to 20mL 9mol / L HCl solution, react at 37°C for 10min, then add 0.3g Ti3AlC2 and continue to react at 37°C for 24h. After the reaction is completed, centrifuge the reaction product at 4000rpm. Discard the supernatant, wash the solid residue with ultrapure water, centrifuge again at 4000rpm, and repeat the operation until the solid residue adheres to the wall of the centrifuge tube. Adjust the centrifuge speed to 8000rpm, centrifuge again, discard the supernatant, wash the precipitate with ultrapure water, and repeat the operation until the pH of the supernatant after centrifugation is greater than 5. Add the precipitate after centrifugation to 35ml of ultrapure water, ultrasonically treat for 13min, centrifuge again at 4000rpm for 20min, take the supernatant, and obtain a MXene nanomaterial aqueous solution with a concentration of 5mg / ml;
[0095] (2) Ultrapure water was used to ultrasonically clean a commercially available PU sponge. The PU sponge was a square of 2cm*2cm*2cm and weighed 0.25g. Ultrasonic cleaning was performed for 20 minutes, and then ultrasonic cleaning was performed in ethanol for 20 minutes. After ultrasonic cleaning was completed, the sponge was dried in an oven at a working temperature of 60°C for 2 hours. The cleaned PU sponge was placed in a 5mg / ml MXene nanomaterial aqueous solution obtained in step (1). The weight ratio of the MXene nanomaterial aqueous solution to the PU sponge was 1.2:1. The sponge was soaked at 25°C for 5 minutes, and then dried in an oven at a working temperature of 60°C for 1 hour. After drying, the sponge was soaked in the MXene aqueous solution again. The soaking and drying cycle was repeated 4 times to obtain a porous material loaded with MXene nanomaterials with a MXene nanomaterial loading of 2% of the weight of the porous material substrate, which was recorded as MXene@PU.
[0096] (3) Wrap the surface of the MXene@PU in step (2) with plastic wrap, with the wrapping area accounting for 85% of the total surface area of the MXene@PU, and fix the wrapped MXene@PU on the top of a container such as polytetrafluoroethylene by pasting, and add 50ul of n-octyltrimethoxysilane to the container, and load n-octyltrimethoxysilane onto the porous material by chemical vapor deposition at a temperature of 50°C for 75min to obtain a porous material with an n-octyltrimethoxysilane loading of 0.1% of the weight of the porous material substrate, recorded as OTMS-MXene@PU.
[0097] 1. Study on the performance of the porous material with oil absorption performance in treating oily wastewater described in this application:
[0098] 0.15 g of crude oil with a viscosity of 1900 mPas was dropped onto the porous material prepared in Example 1 with a weight of 0.25 g and a size of 2 cm*2 cm*2 cm, and adsorbed for 12 min at a temperature of 25° C. The adsorption effect from 0 to 12 minutes was recorded using a contact angle meter (LSA 100, LAUDA scientific). The results are shown in FIG. Figure 2 shown.
[0099] PU sponge and the porous material prepared in Example 4 were used to replace the porous material in Example 1 as control tests, and the above test method was used to adsorb crude oil. The adsorption effect is shown in FIG. Figure 2 shown.
[0100] from Figure 2 It can be seen that the porous material prepared in Example 1 of the present application can completely absorb the crude oil within 2 minutes, and the porous material prepared in Example 4 can completely absorb the crude oil within 6 minutes because the gradient modification of the alkyl silane coupling agent is not performed. That is, constructing the chemical energy gradient of the silane coupling agent can increase the oil absorption rate of the porous material, and the PU sponge cannot completely absorb the crude oil even after 12 minutes.
[0101] 2. Effect of the temperature of oily wastewater on the adsorption performance of the porous material with oil absorption performance described in this application
[0102] 0.5 ml of crude oil with a viscosity of 1900 mPa s was dropped onto two porous materials prepared in Example 1, each weighing 0.25 g. The temperatures of the crude oil were set to room temperature 22° C. and 90° C., respectively. A contact angle meter (LSA 100, LAUDA scientific) was used to record the adsorption effect of the porous material on the crude oil within 0-180 s. The results are shown in FIG. Figure 3 shown.
[0103] from Figure 3It can be seen from the figure that when the temperature of crude oil is 90°C, the porous material can completely absorb the crude oil within 6 seconds, while when the temperature of crude oil is 22°C, the porous material can completely absorb the crude oil within 180 seconds. As the temperature increases, the heat energy absorbed by the crude oil is converted into intermolecular kinetic energy, and its thermal motion increases, which is manifested in the macroscopic decrease of the viscosity of the crude oil. The decrease in viscosity enhances the fluidity of the crude oil and makes it easier to be absorbed by the porous medium or adsorbent. Therefore, the viscosity of the crude oil can be reduced by heating, which increases the diffusion rate and permeability of the crude oil in the porous medium.
[0104] 3. Effect of light on the adsorption properties of the porous material with oil absorption properties
[0105] At 100mw / cm 2 Under a light intensity of , 0.15 g of crude oil with a viscosity of 2500 mPas was dropped onto 0.25 g of the porous material prepared in Example 1 and 0.25 g of the porous material prepared in Example 4, respectively. The temperature of the crude oil was room temperature. An optical camera was used to record the adsorption effect of the porous material on the crude oil within 0-6 minutes. The results are as follows: Figure 4 shown.
[0106] Test results such as Figure 4 As shown:
[0107] from Figure 4 It can be seen that the porous material prepared in Example 1 of the present application has a higher oil absorption efficiency. Figure 2 and Figure 4 It can be seen that under the condition of higher crude oil viscosity (the crude oil viscosity in this experiment is 2500mPas, Figure 2 The viscosity of the crude oil in the experiment was 1900 mPas. The oil absorption time of the two materials was made the same by light irradiation, that is, light irradiation can improve the oil absorption performance of the porous material described in this application.
[0108] 4. Study on the reuse effect of the porous material with oil absorption performance described in this application
[0109] A piece of porous material prepared in Example 1 weighing 0.25 g was soaked in 100 ml of n-hexadecane for 5 min, taken out, weighed and the weight was recorded, then the oil was squeezed out, weighed and the weight was recorded, and then soaked in 100 ml of n-hexadecane for 5 min. The above steps were repeated 10 times to test the reusability of the porous material.
[0110] Test results such as Figure 5 As shown:
[0111] from Figure 5It can be seen that after 10 cycles of soaking and squeezing, the absorption amount of the porous material described in the present application has not been significantly reduced, that is, the porous material described in the present application has good reusability.
[0112] 5. Study on the oil absorption capacity of porous materials with oil absorption properties described in this application
[0113] Three pieces of porous materials prepared in Example 1, each weighing 0.25 g, were soaked in 100 ml of hexadecane, diesel and dodecane for 5 min respectively. After the soaking was completed, the materials were taken out and weighed and recorded.
[0114] Test results such as Figure 6 As shown:
[0115] from Figure 6 It can be seen that the porous material can absorb crude oil 20-30 times its own weight, that is, the porous material described in this application has a very high oil absorption capacity.
[0116] 6. Effect of different loading amounts of silane coupling agent on the adsorption performance of the porous material with oil absorption performance described in this application
[0117] At 100mw / cm 2 Under a light intensity of , 0.5 ml of n-hexadecane with a viscosity of 3 mPas was dropped onto 0.25 g of the porous material prepared in Example 5. An optical camera was used to record the adsorption effect of n-hexadecane on the porous material after 30 minutes. The results are as follows: Figure 7 shown.
[0118] from Figure 7 It can be seen that the n-hexadecane dripped onto the surface of the porous material in Example 5 was not completely absorbed within 30 minutes, that is, excessive loading of silane coupling agent is not conducive to the porous material's adsorption of crude oil.
[0119] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A porous material with oil absorption performance, characterized in that: It includes a porous material substrate, a MXene nanomaterial loaded on the porous material substrate, and an alkyl silane coupling agent.
2. The porous material with oil absorption performance according to claim 1, characterized in that: The porous material substrate includes one or more of a polyurethane sponge substrate, a melamine sponge substrate and a wood sponge; And / or, the silane coupling agent includes one or more of methyltrimethoxysilane, ethyltrimethoxysilane and n-octyltrimethoxysilane; And / or, the loading amount of the MXene nanomaterial on the porous material substrate is 1%-3% of the weight of the porous material substrate; And / or, the loading amount of the silane coupling agent on the porous material substrate is 0.04%-0.06% of the weight of the porous material substrate; Preferably, the silane coupling agent is distributed in a gradient manner on the porous material substrate, and the loading amount of the silane coupling agent gradually decreases from the surface to the interior of the porous material substrate.
3. The method for preparing the porous material having oil absorption performance according to any one of claims 1 to 2, characterized in that: The following steps are involved: (1) soaking the porous material substrate in an aqueous solution of MXene nanomaterials, and drying the substrate after soaking to obtain a porous material loaded with MXene nanomaterials; (2) Loading the silane coupling agent onto the porous material loaded with the MXene nanomaterial by chemical vapor deposition to obtain the porous material with oil absorption performance.
4. The method for preparing a porous material having oil absorption performance according to claim 3, characterized in that: In step (1), the concentration of the MXene nanomaterial aqueous solution is 3 mg / ml-7 mg / ml; And / or, the volume ratio of the porous material substrate to the MXene nanomaterial aqueous solution is 1:(1.2-2); And / or, the soaking temperature is 25°C-35°C, and the soaking time is 4min-6min; And / or, the drying temperature is 50° C.-70° C., and the drying time is 50 min-70 min.
5. The method for preparing a porous material having oil absorption performance according to claim 3, characterized in that: In step (2), the surface of the porous material loaded with MXene nanomaterials is coated and then subjected to chemical vapor deposition; Preferably, the area of the porous material surface loaded with MXene nanomaterials that is wrapped accounts for 80%-90% of its total surface area; Preferably, the surface of the porous material loaded with MXene nanomaterials is wrapped with plastic wrap.
6. The method for preparing a porous material having oil absorption performance according to any one of claims 3 to 5, characterized in that: In step (2), the weight ratio of the silane coupling agent to the porous material loaded with MXene nanomaterial is (0.8-1.2): 2000; And / or, the temperature of the vapor deposition is 25° C.-35° C.; the time of the vapor deposition is 1 h-1.5 h.
7. The method for preparing a porous material having oil absorption performance according to any one of claims 3 to 5, characterized in that: The preparation method further comprises cleaning the porous material substrate; Preferably, the porous material substrate is subjected to ultrasonic cleaning treatment in water and ethanol in sequence.
8. A method for treating oily wastewater, characterized in that: The porous material with oil absorption performance described in any one of claims 1 to 2 or the porous material with oil absorption performance obtained by the preparation method described in any one of claims 3 to 7 is used to adsorb and treat oily wastewater.
9. The processing method according to claim 8, characterized in that: The viscosity of the oil in the oily wastewater is 0-2500 mPas; And / or, the oil concentration in the oily wastewater is greater than 10 ml / m 3 .
10. The processing method according to claim 8 or 9, characterized in that: The treatment temperature is 20°C-90°C, and the treatment time is 4-6 minutes; And / or, the treatment is carried out under light conditions, preferably, the light intensity is 60mw / cm 2 -150mw / cm 2 .